Learning styles of students in the 3rd year of high school from the New ILS (New Index of Learning Styles) (Research, Society and Development, 2020)
This study aimed to analyze the Learning Styles of 25 students from a third-year high school class of a state school located in the municipality of Rio Sono in Tocantis - TO. The Learning Styles reflected as individuals' educational selections and their possible knowledge that the teacher can interfere in the use of different methodological methods as a way to favor the teaching and learning process. In this research it was possible to verify that in the same class there are students with different learning styles and, also, different levels of preference. It is considered that student-oriented learning favors their understanding of the contents, but the teacher must know how to balance his teaching methodologies for the purpose of studying students' learning styles, when necessary, so that they can leave their zone of comfort and adding different skills.